Livestock Feed Test Using Fermented Coffee Skin, Okara and Beef Bone for Broiler Chickens - Andrew Setiawan Rusdianto; Andi Eko Wiyono; Sri Wahyuni; Ucik Nurul Hidayati (Agroindustrial Technology Journal, 2021)
Coffee skin waste is the side result of the process of coffee processing. The coffee skin contains a crude protein of 10.4% which can help the growth in broiler chickens. Coffee skin composition consisting of high coarse fiber and anti-nutritional content,so it is necessary to do fermentation to increase the nutrient content in the skin of coffee and reduce the content of anti-nutritional substances. Proteins in the skin of coffee need the addition of protein from okara to meet the protein needs of broilerchickens. Other than protein, livestock feed for broiler chickens should also contain calcium, which is obtained from the beef bones. This research aims to determine the protein content of feed and the effect of artificial feed on feed consumption, daily weight gain as well as conversion of broiler chickens feed. This study uses complete random design (RAL). Feeding with 5 treatments, 2 repeats and each repetition consists of 1 broiler chickens. The results of the research on protein test showed the protein content of coffee skin feed, okara and beef bones contain 28.82% protein. The test results on feed consumption showed the highest consumption rate was P0 with 2023 g and the lowest was P4 with 888 g. The highest daily weight gain test was P1 treatment, which was 82.525 g treatment and the lowest of the was P4 for 61.25 g. The highest feed conversion value is P0 with 26.42 and the lowest is P4 for 14.495